Differences in EMG activity when exercising on a static and moving rowing machine - Baca, A.; Schöllauf, V.; Kornfeind, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Rowing machines are used for land-based training in periods of bad weather conditions. Two main modes of operation can be distinguished. In the static mode, the foot stretcher is stationary and the rower moves relative to the static rowing simulator. If the simulator itself rolls back and forth during the rowing stroke, a motion more similar to outdoor rowing may be expected (Elliott et al., 2002). Whereas comparisons of kinematics and reaction forces between the two modes have been reported (Kleshnev, 2005; Baca et al., 2006; Colloud et al., 2006), no such studies for EMG activity can be found. Methods: Seven Austrian female and male subjects (21.0±2.5 yr) with international competition experience participated in the study. A Concept2 (Concept2, Vermont, USA) rowing machine was operated both in the static mode and on slides (a construction that is attached to the legs), enabling rolling back and forth. The subjects exercised with 18 and 30 strokes per minute (SR18, SR30). EMG signals were derived from the m. biceps brachii (BB), m. triceps brachii (TB), m. deltoideus posterior (DP), m. teres major (TM), m. erector spinae (ES), m. vastus lateralis (VL), m. biceps femoris (BF) and m. gastrocnemius medialis (GM) with a wireless Delsys system (Bagnoli DesktopEMG) on the right side of the body. Results: Significant differences (Wilcoxon, p<0.05) could be found for the pre-activation (ratio of the EMG amplitude at the beginning of the pulling phase and the maximum amplitude) of VL (SR18), BF (SR18) and GM (SR18, SR30), the maximum of the EMG-signals of BB (SR18, SR30), TB (SR30), DP (SR18, SR30), TM (SR18, SR30), ES (SR30) and VL (SR18, SR30), which was normalized to the average power during the pulling phase, the integral of the thus normalized EMG-data during the pulling phase of BB (SR18, SR30), DP (SR18, SR30), ES (SR30) and VL (SR18, SR30) as well as the duration from the beginning of the pulling phase until the maximum EMG-amplitude for DP (SR 30), TM (SR30) and GM (SR30). Discussion: The present study suggests that the choice of the rowing machine influences muscular adaptation and affects the rowers` motor control pattern. Differences (in particular between pre-activation and the maximum amplitudes) are supposed due to different masses (rowing machine vs. body mass of subject) having to be accelerated/decelerated at the beginning of the pulling phase. Comparative studies in on-water rowing are required in order to draw further conclusions regarding the advantage of a specific rowing simulator modality.